1989
DOI: 10.1677/joe.0.123r013
|View full text |Cite
|
Sign up to set email alerts
|

An Enzyme-Linked Immunosorbent Assay for Cortisol in the Saliva of Man and Domestic Farm Animals

Abstract: An enzyme-linked immunosorbent assay has been developed for the direct assay of cortisol in the saliva of man, sheep, calf and pig. The assay is sensitive (integral of 1pg), highly specific and reproducible, and has the advantage over radioimmunoassay in being cheaper and quicker to carry out. The relatively-non invasive method of collecting saliva on cotton buds coupled with simple assay equipment provide a good potential for assessing cortisol status in studies on stress and welfare in farm animals as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
3

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 10 publications
4
34
0
3
Order By: Relevance
“…avoiding the variations due to blood sampling or restraint stress) some authors have proposed detecting it in different biological materials, such as saliva (Cooper et al, 1989), milk (Shutt and Fell, 1985;Verkerk et al, 1998), faeces and urine (Hay and Mormede, 1998). The level of the cortisol is in some equilibrium with the different compartments and the sampling of these materials is, generally, considered less invasive.…”
Section: Cortisolmentioning
confidence: 99%
“…avoiding the variations due to blood sampling or restraint stress) some authors have proposed detecting it in different biological materials, such as saliva (Cooper et al, 1989), milk (Shutt and Fell, 1985;Verkerk et al, 1998), faeces and urine (Hay and Mormede, 1998). The level of the cortisol is in some equilibrium with the different compartments and the sampling of these materials is, generally, considered less invasive.…”
Section: Cortisolmentioning
confidence: 99%
“…Although traditionally cortisol concentrations have been determined in plasma or serum, their determination in other fluids or organic tissues (saliva, milk, muscle, urine, faeces and hair) can be of interest in animal welfare studies of different species (Cooper et al, 1989;Fritsche and Steinhart, 1998;Verkerk et al, 1998;Cirimele et al, 1999;Fritsche et al, 1999;Antignac et al, 2000;Morrow, 2000;Palme et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…or salivary cortisol has been used as a biomarker of stress (Cooper et al 1989, Beerda et al 1996, Whitten 1998, Dreschel & Granger 2005, Hellhammer et al 2009, Montanha et al 2009. It has been shown that salivary and plasma levels of cortisol are correlated (Beerda et al 1996) and the measure of the basal cortisol levels in domestic cats using saliva samples was previously studied and validated (Siegford et al 2003).…”
Section: Introductionmentioning
confidence: 99%